2019
DOI: 10.1007/s00005-019-00543-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antidepressants on the Immune System

Abstract: Depression is one of the most frequently diagnosed condition in psychiatry. Despite the availability of many preparations, over 30% of treated patients do not achieve remission. Recently the emphasis is put on the contribution of the body’s inflammatory response as one of the causes of depression. The interactions between nervous and immune systems are the main issue addressed by psychoneuroimmunology. In patients suffering from depression changes in the plasma concentrations of cytokines and in the number and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 67 publications
(79 reference statements)
0
51
0
1
Order By: Relevance
“…Antidepressants have been consistently shown to have anti-inflammatory proprieties, although little is known about their possible role in systemic infections [ 38 , 54 , 84 ]. In vitro studies showed a protective effect against bacteria and fungi [ 26 ], but clinical data are unclear, as a possibly higher risk of Clostridium difficile infection has been reported [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antidepressants have been consistently shown to have anti-inflammatory proprieties, although little is known about their possible role in systemic infections [ 38 , 54 , 84 ]. In vitro studies showed a protective effect against bacteria and fungi [ 26 ], but clinical data are unclear, as a possibly higher risk of Clostridium difficile infection has been reported [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin can influence the unbalanced release of monoamine neurotransmitters—such as serotonin (5-HT), dopamine (DA), noradrenaline, and glutamate—the expression of monoamine oxidase (MAO), the expression of neurotrophic factors such as brain-derived neurotrophic factor (BDNF) and neurogenesis, as well as the dysregulated immune system function and oxidative and nitrosative stress. Thus, curcumin appears to promote neurogenesis and inhibit neuronal cell apoptosis [ 83 , 84 , 92 , 93 ]. Despite the consistent evidence of efficacy and safety of curcumin treatment in other pathological conditions, to date, data on its effects on depression in pregnancy are completely lacking.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…In the interim guidance document of WHO, when the novel coronavirus was suspected, it was mentioned that utilizing vasopressors (norepinephrine, epinephrine, and dopamine most safely received from a central venous catheter) helps clinicians in managing the patients with acute respiratory failure and septic shock, as a consequence of severe infection. 57,85,86 Based on the described role of host immune responses, in overcoming the infection disease, it has been recommended that serotonergic and dopaminergic pathways are attractive targets to treat the human infectious disease. For example, fluoxetine, by its action on the serotonergic pathway in the central nervous system, regulates the neuroendocrine signals and also modulates the immune response against infection.…”
Section: Discussion About Suggested Strategymentioning
confidence: 99%